Solvency, Profitability, Company Size, and Public Accounting Firm Size (KAP) Towards Timeliness - Herlan; Chasbiandani, Tryas; Mudya Putri, Desylva (Action Research Literate, 2024)
The purpose of this research is to test empirically the effect of solvency, profitability, company size and the size of a public accounting firm on the timeliness of property and real estate companies listed on the Indonesia Stock Exchange in 2019-2021. This study uses data from 86 property and real estate companies that have been selected using a purposive sampling method with a total of 25 data for three years. The data used is secondary data in the form of financial reports. Data processing in this study uses Statistical Product and Service Solutions (SPSS) version 25. The results of this study indicate that solvency has no significant effect on timeliness, profitability has a significant effect on timelines, company size has a significant effect on timeliness, and the size of a public accounting firm has no significant effect against timeliness